(untitled) (Veterinária Notícias, 2022)
The importance of Brazil for the international trade of poultry products induces legislators and interested companies to pay attention to complying with international standard quality requirements. One of these requirements is the suppression of the indiscriminate use of antibiotics in poultry, as in the strategy of use as a growth promoter. To meet this demand, the study of short-chain organic acids becomes interesting and their review essential. As good examples for the issue described, short chain organic acids such as citric acid, fumaric acid, sorbic acid and malic acid are extremely important due to their antimicrobial qualities, accessibility and international acceptance. In addition to the individual effect, the blend of acids, that is, the association of acids for the role of growth promoter or performance enhancer, combines acids that act synergistically, enhancing their qualities. This study aims to address the physicochemical characteristics, effects and qualities of short-chain organic acids, as well as their associated effect, encouraging further work that fills the scientific gaps in empirical knowledge about these additives.